Patient with bilateral breast enlargement and hypospadias - Ali, Abu Ahmed Ashraf; Ahmed, T; Rashid, MM (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):104-108. The abstract of this article is available on the PubMed website